Initiating financial technology regulation based on Islamic legal principles - Nurrachman, Alfan Dzikria (Privietlab, 2025)
This article aims to determine the regulations regarding Sharia financial technology, as regulated in the Regulation of the Financial Services Authority of the Republic of Indonesia Number 40/2024 concerning Information Technology-Based Joint Funding Services (LPBBTI). This study uses an empirical juridical approach with primary data in the form of interviews with funders and Sharia fintech operators. The results of this study indicate that the regulation of Sharia fintech based on POJK Number 40/2024 concerning LPBBTI presents characteristics in the form of ecosystem-based financing, with the spirit built being the distribution of funds to support productive activities. The organizers themselves also provide insurance protection in the distribution of financing and cooperate with certain companies to provide periodic guidance on every productive activity.